Disaster Impact Across Cultural Groups: Comparison of Whites, African Americans, and Latinos. Issue 1 (25th May 2013) - Davidson, Tatiana M.; Price, Matthew; McCauley, Jenna L.; Ruggiero, Kenneth J.
Abstract: The current study extends knowledge regarding the differential impact of natural disasters among White, African American, and Latino survivors of Hurricane Ike through its use of a large, regional sample recruited via representative sampling procedures to examine the associations between cultural identification and disaster impact, including loss, damage, and negative mental health outcomes. Consistent with previous research, results indicated disparities between cultural groups with regard to disaster exposure. Additionally, type of disaster impact was differentially associated with PTSD and depression status dependent on cultural group. Specifically, the extent of personal disaster exposure, property damage, and loss of services made significant contributions to PTSD status among White survivors. African‐Americans were more likely than White and Latino Ike survivors to endorse post‐disaster PTSD and depression and endorsement of depression was predicted by severity of property damage. With respect to Latino respondents, only the extent of personal disaster exposure significantly contributed to both PTSD and depression status. Implications of the current findings are discussed with regard to future disaster preparedness and response efforts and the implementation and evaluation of community‐based disaster resources.